Halo Mongolian spot. - Pisani, V. (European Journal of Pediatric Dermatology, 2016)
Despite being given the occurrence of a vitiligo halo around several lesions from common melanocytic nevi to neuroid nevi, neurofibromas, blue nevi and melanomas (2), we did not find in the literature cases of vitiligo halo around Mongolian spot. What we have observed recalls a less rare phenomenon, namely the regression of Mongolian spot around café au lait spots in peripheral neurofibromatosis. In these cases, the area of normal skin that forms around a café au lait spot of the lumbosacral region affected by Mongolian spot seems due to regressive phenomena of dermal dendritic melanocytes and not rather to an alteration of melanocytes of the dermo-epidermal junction that appear normally pigmented (1). Another difficult to interpret aspect is the dermo-hypodermic hypoplasia below Mongolian spot, perhaps an associated defect nevus.